2019
DOI: 10.1007/s00018-019-03119-z
|View full text |Cite
|
Sign up to set email alerts
|

The zinc-finger transcription factor MAZR regulates iNKT cell subset differentiation

Abstract: Invariant natural killer T (iNKT) cells represent a subgroup of innate-like T cells and play an important role in immune responses against certain pathogens. In addition, they have been linked to autoimmunity and antitumor immunity. iNKT cells consist of several subsets with distinct functions; however, the transcriptional networks controlling iNKT subset differentiation are still not fully characterized. Myc-associated zinc-finger-related factor (MAZR, also known as PATZ1) is an essential transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…This result confirms our original study, where we reported the NKT cell proportion among NKT cells to vary between 0.2% and 0.5% in 2‐ to 5‐week‐old C57BL/6 mice 34 . However, numerous studies investigating NKT cell development report a higher proportion, varying from 3% to 17% . The unusually high proportion of HSA high NKT cells reported in these studies may be a result of the absence of enrichment strategies or inefficient application of such strategies, resulting in contamination of the HSA high NKT cell with conventional T cells or cortical thymocytes.…”
Section: Nkt Cell Identification During Positive Selectionsupporting
confidence: 89%
“…This result confirms our original study, where we reported the NKT cell proportion among NKT cells to vary between 0.2% and 0.5% in 2‐ to 5‐week‐old C57BL/6 mice 34 . However, numerous studies investigating NKT cell development report a higher proportion, varying from 3% to 17% . The unusually high proportion of HSA high NKT cells reported in these studies may be a result of the absence of enrichment strategies or inefficient application of such strategies, resulting in contamination of the HSA high NKT cell with conventional T cells or cortical thymocytes.…”
Section: Nkt Cell Identification During Positive Selectionsupporting
confidence: 89%
“…In line with the role PATZ1 in antagonizing ZBTB7B and CD4 expressions in conventional T cells ( 106 , 107 ), PATZ1-deficient iNKT cells express increased levels of CD4 and ZBTB7B, and moreover, the combined loss of PATZ1 & RUNX3 results in a further increase of ZBTB7B, accompanied with enlarged/reduced proportions of iNKT2/iNKT17 cells, respectively ( 108 ). Additionally, PATZ1-deficient iNKT cells express more EGR2 ( 108 ), which controls iNKT lineage differentiation and is normally expressed at the highest level in iNKT2 cells, followed by iNKT17 and iNKT1 cells ( 61 , 109 ). Considering the aforementioned roles of ZBTB7B in iNKT development ( 97 , 98 , 101 , 102 ), it seems that PATZ1 regulates the subset differentiation of iNKT cells mainly by fine-tuning expressions of ZBTB7B and EGR2.…”
Section: Zbtb Proteins Regulating Both the Development And Function Omentioning
confidence: 80%
“…T-cell specific depletion of PATZ1 (Lck-Cre) results in an increased number of IL-4-producing iNKT2 cells at the expense of iNKT1 and iNKT17 cells ( Figure 1B ), but the total number of iNKT cells as well as their survival & proliferation is not affected ( 108 ). In line with the role PATZ1 in antagonizing ZBTB7B and CD4 expressions in conventional T cells ( 106 , 107 ), PATZ1-deficient iNKT cells express increased levels of CD4 and ZBTB7B, and moreover, the combined loss of PATZ1 & RUNX3 results in a further increase of ZBTB7B, accompanied with enlarged/reduced proportions of iNKT2/iNKT17 cells, respectively ( 108 ). Additionally, PATZ1-deficient iNKT cells express more EGR2 ( 108 ), which controls iNKT lineage differentiation and is normally expressed at the highest level in iNKT2 cells, followed by iNKT17 and iNKT1 cells ( 61 , 109 ).…”
Section: Zbtb Proteins Regulating Both the Development And Function Omentioning
confidence: 99%
“…PATZ1 belongs to the POZ and Krüppel (POK) family of transcription factors, which are implicated in many biological processes, including B cell fate determination, cell cycle progression, DNA damage responses and development (gastrulation, limb formation, hematopoietic stem cell fate determination) (Kelly and Daniel, 2006;Costoya, 2007). Accordingly, Patz1 has been implicated in T cell differentiation (Ellmeier, 2015;Andersen et al, 2019;Orola et al, 2019), cell cycle regulation (Valentino et al, 2013b), DNA damage response (Keskin et al, 2015), and embryonic development (Valentino et al, 2013b). Noteworthy, a critical role for Patz1 has been described in the maintenance of embryonic stemness through its functional interaction with the pluripotency master genes Nanog and Pou5f1, which are both targets and regulators of Patz1 (Ow et al, 2014).…”
Section: Introductionmentioning
confidence: 99%